Efforts In Improving Serve Learning Outcomes Using Exercises Variation On Volleyball Games At SD 228 Of North Bengkulu Regency - Rio Widiansyah Rizki; Azizatul Banat; Deffri Anggara (Sinar Sport Journal, 2022)
This research is motivated by several problems in physical learning at SDN 228 North Bengkulu. One of the problems is that students are reluctant to take part in sports exercises organized by the teacher because they find these exercises tiring. This study aims to determine the extent to which serve learning outcomes increased using a variety of training methods in volleyball games in Class V SD Negeri 228, of North Bengkulu Regency. This type of research is classroom action research which consists of 2 cycles with steps; planning, action, observation, and reflection. The research subjects were 20 fifth grade students at SDN 228 of North Bengkulu Regency. The research instrument used was the over serve test and the under serve test. The results of the study proved that the exercise variation method was able to improve service learning outcomes in volleyball games at SD Negeri 228 of North Bengkulu Regency with an increase in the average score in cycle I, which was 65 and increased to 75 in cycle II. In addition, the results of the observation sheet also show that the quality of learning volleyball using a variety of exercises in cycle 2 is better than the previous cycle. This can be seen from the results of the observation sheet which has reached a very high category with a percentage of 100%. Mastery of the material and the use of learning resources and learning media has been very effective carried out by researchers. Thus, it can be concluded that the training variation method is very effective in improving service learning outcomes in volleyball games at SDN 228 of North Bengkulu.